THE DISPLAYS OF GENERAL TENDENCIES IN THE AREA OF FERRARI CAR TECHNOLOGY - LAVRINCIK, Jan (Trends in education, 2008)
The article presents some of the novelties in problems of Ferrari and Formula 1 terminology. The borrowing of the words from English, French, and Italian is emphasized. The significance of prefixes and suffixes is mentioned, and the use of commercial titles for modern materials used in construction is explained.
Keywords: terminology; term; Ferrari; Formula 1; prefix; suffix.